Adverse Effects of Oral Hypoglycemic Agents and Adherence to them among Patients with Type 2 Diabetes Mellitus in Nepal - Manandhar Shrestha, Jyoti Tara; Shrestha, Himal; Prajapati, Miyasha; Karkee, Astha; Maharjan, Aman (Journal of Lumbini Medical College, 2017)
Introduction: Oral hypoglycemic agents (OHAs) are the most common drugs used in Type 2 Diabetes Mellitus. There are various established adverse effects related to their use including hypoglycemia, weight gain, gastrointestinal disturbance, lactic acidosis, and fluid retention. However, the pattern of adverse effects related to OHAs in Nepalese patients still needs to be explored. Our study aims to determine the pattern of adverse effects resulting from the use of OHAs among Type 2 Diabetes mellitus patients and their adherence to the medication. Methods: All diabetic patients who met the inclusion criteria were enrolled in the study. After informed consent, patients were interviewed and evaluated as per the designed proforma. They were mainly studied for common drug used, adverse effects of the drugs, occurrence of hypoglycemia, and adherence to treatment. Results: The study comprised of 183 patients with mean age of 58.73 years (SD = 12.95). Fifty-six (30.6%) patients said that they developed adverse effects of drugs but only 21 (11.5%) of them reported to their treating physician. Most common adverse effect were related to central nervous system such as tingling sensation of hands and feet, dizziness, drowsiness, etc. Though 91 (49.7%) patients had developed symptoms suggestive of hypoglycemia, only 31 (16.9%) knew that it was due to hypoglycemia. Majority of the patients (n = 143, 78.1%) administered the drugs as prescribed by the physician. Among the defaulters, the most important reasons for failure to properly administer the drugs was forgetfulness in 82.5% (n = 33, N = 40) of cases. Among the study variables family history of chronic illness (p = 0.046) and information about adverse effects from physician (p = 0.001) had a significant relationship with incidence of adverse effects. Whereas none of them had a significant relationship with adherence to hypoglycemic medication. Conclusion: The incidence of adverse effects was high with hypoglycemia occurring in 49.7% of the cases, though only one-third of them recognized it to be due to hypoglycemia, in the patients with Type 2 Diabetes Mellitus. Family history of chronic illness and information about adverse effects from the physician had significant relationship with the incidence of adverse effects of hypoglycemic treatment. Journal of Lumbini Medical College Vol 5, No 1, Jan-June 2017, page: 34-40 DOI: https://doi.org/10.22502/jlmc.v5i1.126